A mixed-method approach to assess business models of communication departments: insights from a pilot study - Link, Jeanne; Vaassen, Fiona; Lautenbach, Christoph; Zerfass, Ansgar (Frontiers in Communication, 2025)
PurposeThe article introduces and evaluates a method for applying a new management tool for corporate communications and public relations: the Communication Business Model (CBM).Design/methodology/approachThe conceptual development of a multidimensional method for identifying, analyzing, and assessing business models of communication departments is combined with an evaluation study providing empirical findings from a pilot project with 53 communication departments.FindingsThe results of the study show that the CBM approach works in practice, as four distinct business models could be identified. The validity of the proposed assessment method is substantiated. Prerequisites, obstacles, and success factors for using the method are identified.Research limitations/implicationsThe article reports about the first application of the business model approach – a well-known concept in general management – to communication departments. However, as the findings refer to a pilot study, future research is required to test and validate the tool in a wider range of organizations and contexts.Originality/valueThe study shows how research in the field of communication management and public relations can be translated into practice and how the success of such efforts can be evaluated. Developing, applying, and testing a method for using a management tool that addresses a long-standing leadership challenge helps communication leaders apply theoretical knowledge to their daily work.